2017
DOI: 10.3389/fpsyt.2017.00163
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Objectifies the Diagnosis of Psychiatric Disorders: A Literature Review

Abstract: BackgroundTo date, a diagnosis in psychiatry is largely based on a clinical interview and questionnaires. The retrospective and subjective nature of these methods leads to recall and interviewer biases. Therefore, there is a clear need for more objective and standardized assessment methods to support the diagnostic process. The introduction of virtual reality (VR) creates the possibility to simultaneously provoke and measure psychiatric symptoms. Therefore, VR could contribute to the objectivity and reliabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 68 publications
(81 reference statements)
2
35
1
2
Order By: Relevance
“…VR versions of the RAM were also used to assess the integrity of the hippocampus – predicting risk or severity in a variety of psychiatric disorders ( Astur et al, 2005 ; Wilkins et al, 2017 ). Such insights are in line with the growing trend of using VR to provide objective diagnostic metrics ( Cogné et al, 2017 ; van Bennekom et al, 2017 ). For instance, Migo et al (2016) identified behavioral and neural correlates of completing the RAM task in patients with amnestic mild cognitive impairment (MCI), which extends upon the work of King et al (2002) who showed that when changing virtual viewpoints, MCI patients could not recall the positions of objects.…”
Section: Harnessing the Affordances Of Vr To Aid Memory Researchsupporting
confidence: 75%
See 1 more Smart Citation
“…VR versions of the RAM were also used to assess the integrity of the hippocampus – predicting risk or severity in a variety of psychiatric disorders ( Astur et al, 2005 ; Wilkins et al, 2017 ). Such insights are in line with the growing trend of using VR to provide objective diagnostic metrics ( Cogné et al, 2017 ; van Bennekom et al, 2017 ). For instance, Migo et al (2016) identified behavioral and neural correlates of completing the RAM task in patients with amnestic mild cognitive impairment (MCI), which extends upon the work of King et al (2002) who showed that when changing virtual viewpoints, MCI patients could not recall the positions of objects.…”
Section: Harnessing the Affordances Of Vr To Aid Memory Researchsupporting
confidence: 75%
“…VR technologies can also bolster the ecological validity of fMRI for researchers and clinicians to obtain objective diagnostic metrics for patient populations ( King et al, 2002 ; Plancher et al, 2012 ; Cogné et al, 2017 ; van Bennekom et al, 2017 ). With HMDs, cross-institutional collaboration can be facilitated as participants immersed in VR will not be cognizant of the real-world environmental cues.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, in this context a critical literature review reveals a shortage of studies on applications and use of VR. Indeed, few studies of this type exist, related to areas such as gaming (Makri & Vlachopoulos, 2017), medicine (van Bennekom, Koning & Denys, 2017;Howard, 2017) and education (Hainey, Connolly, Boyle, Wilson & Razak, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Its applications are vast, ranging from military training to gaming. In medicine, the technology has been trialed for uses such as cognitive rehabilitation post-stroke ( 3 ), improving reaction times in children with cerebral palsy ( 4 ) and in aiding the diagnosis of psychiatric conditions ( 5 ).…”
Section: Introductionmentioning
confidence: 99%